2007
DOI: 10.1021/ef060547k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mercury Transformation by HBr Addition in a Slipstream Facility with Real Flue Gas Atmospheres of Bituminous Coal and Powder River Basin Coal

Abstract: An investigation of speciated mercury transformation with the addition of hydrogen bromide (HBr) at elevated temperatures was conducted in a slipstream reactor with real flue gas atmospheres. A real flue gas atmosphere is composed of bituminous coal (with high sulfur and high chlorine contents) and Powder River Basin (PRB) coal (with lower sulfur and chlorine contents). The average sulfur, chlorine, and mercury contents in the tested bituminous coal were 1.31% and 1328 and 0.11 ppm and 0.61% and 170 and 0.08 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…2. This HCl concentration represented the concentration in a typical combustion of bituminous and sub-bituminous coal with medium chlorine content [27,28]. Our experimental results indicated that carrier gases evaluated in this study had significant effects on Hg-oxidation.…”
Section: Role Of Carrier Gas In Hg-oxidationmentioning
confidence: 56%
“…2. This HCl concentration represented the concentration in a typical combustion of bituminous and sub-bituminous coal with medium chlorine content [27,28]. Our experimental results indicated that carrier gases evaluated in this study had significant effects on Hg-oxidation.…”
Section: Role Of Carrier Gas In Hg-oxidationmentioning
confidence: 56%
“…380 °C) increased from a baseline of 18À42 to 96% when the measured bromine concentration in the flue gas increased to 3.5 ppmv. Energy & Fuels ARTICLE Cao et al 21,22 and Qu et al 23 suggested that the simultaneous presence of bromine and chlorine can affect mercury oxidation through the formation of the reactive interhalogen species, BrCl, and thus increase mercury oxidation relative to each halogen by itself. In this work, no such synergy between bromine and chlorine was observed.…”
Section: ' Resultsmentioning
confidence: 99%
“…Cao et al 16,17 suggested that the simultaneous presence of bromine and chlorine can also affect the extent of mercury oxidation due to interhalogen species interactions with elemental mercury. Based on experimental oxidation levels that were higher than expected, they suggested that bromine is able to increase mercury oxidation kinetics by promoting the formation of activated chlorine.…”
Section: Effects Of Mixtures Of Bromine and Chlorine On Homogeneous Oxidationmentioning
confidence: 99%